2020
DOI: 10.1186/s12884-020-03027-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cesarean section on neonatal outcomes at a university-based tertiary hospital in Jordan

Abstract: Background: Over the past two decades, there has been a steady rise in the rate of Cesarean section delivery globally. As a result, short-term and long-term maternal and neonatal complications are rising. The objective of this study is to determine the rate and indications for Cesarean section at King Abdullah University Hospital (KAUH) in Jordan and to assess the resulting neonatal outcomes. Methods: A retrospective chart review was conducted for all women and neonates delivered by Cesarean section during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
1
22
0
4
Order By: Relevance
“…The risk of injury in infants is low but not absent. A high rate of elective CDs has contributed to the increase of fetal complications: respiratory morbidity (respiratory distress syndrome, transient tachypnea of the newborn), admission to the NICU, and increased length of hospitalization, with a significant medical, social, and financial impact on families and medical institutions [7,[11][12][13][14][15]. The adverse risks of CD at 37-38 weeks of gestation significantly increase, with a magnitude of 9-40% [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of injury in infants is low but not absent. A high rate of elective CDs has contributed to the increase of fetal complications: respiratory morbidity (respiratory distress syndrome, transient tachypnea of the newborn), admission to the NICU, and increased length of hospitalization, with a significant medical, social, and financial impact on families and medical institutions [7,[11][12][13][14][15]. The adverse risks of CD at 37-38 weeks of gestation significantly increase, with a magnitude of 9-40% [15].…”
Section: Resultsmentioning
confidence: 99%
“…During spontaneous labor, fetal lung fluid secretion decreases and absorption increases, and stimulation of surfactant release may be mediated by elevated fetal catecholamines in response to rupture of the membranes and delivery. Thus, if CS is performed before the onset of labor, the concentration of catecholamines in the serum does not increase [11,13,14]. Studies have found that full-term neonates born via elective CS have significantly lower catecholamine levels and changes in lung function than those born vaginally [14].…”
Section: Resultsmentioning
confidence: 99%
“…It is lower than the rates of 17.69% to 38.8% reported by authors in other centres [5-7, 18, 19] . Tahir et al [20] in Abbottabad and Khasawneh et al [21] in Jordan reported a CSR of 46.7% and 50.5% respectively. The differences in the CSR reflect differing geographical locations, practice patterns and biodemography characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is also in line with other studies that found prematurity was significantly associated with an increased risk of NICU admission and neonatal mortality. 32,50 Neonates with respiratory depression at birth had seventeen percent excess risk to develop immediate adverse outcomes than those without respiratory depression. Since neonates with respiratory depression may have impeding meconium aspiration, Respiratory Acidosis, prematurity, Encephalopathy, and Hypoxia requiring resuscitation and admission to the NICU.…”
Section: Dovepressmentioning
confidence: 99%